An exploratory comparative analysis of fiscal discipline in Islamic economics: Integrating ethical governance with sustainable financial practices - Andriansyah, Yuli; Atmaja , Fajar Fandi; Lana, Rima Isfah; Azmi, Ghitha Nabilah; Mešković, Admir (Universitas Islam Indonesia, 2025)
IntroductionIslamic economics offers an ethical alternative to conventional financial systems, integrating moral principles derived from the Qur’an and Hadith. While conventional fiscal discipline primarily emphasizes budgetary balance, Islamic fiscal discipline uniquely prioritizes ethical governance, social justice, and sustainable development through instruments such as zakat, waqf, and sukuk.ObjectivesThis study aims to develop a comprehensive model for fiscal discipline based on Islamic economic principles, highlighting ethical dimensions alongside practical financial management considerations.MethodThe research employs an exploratory approach using qualitative analysis of secondary data sourced from scholarly articles, government publications, and case studies. A comparative analytical method assesses fiscal discipline practices in both Islamic and conventional economic frameworks.ResultsThe findings reveal that integrating Islamic financial instruments like zakat, waqf, and sukuk enhances resource allocation, promotes socio-economic equity, and supports sustainable fiscal policies. Effective governance structures, notably Shariah boards, play critical roles in ensuring compliance with Islamic ethical standards. However, there remains a notable gap between theoretical Islamic economic principles and their practical implementation in contemporary fiscal policies.ImplicationsThis research offers policymakers a viable framework for adopting Islamic fiscal discipline, potentially leading to greater economic stability, reduced inequality, and more sustainable development practices. It emphasizes the importance of ethical governance and community participation in fiscal policy formulation and implementation.Originality/NoveltyThe study uniquely bridges theoretical Islamic economic principles with modern fiscal management practices, proposing a holistic and ethically-informed model of fiscal discipline adaptable across various economic contexts.